Evolving Leadership Theories: Integrating Contemporary Theories for VUCA Realities - Vildan Esenyel (Administrative Sciences)
The present study examines the correlation between current leadership models and three key elements of contemporary society: the volatile, uncertain, complex, and ambiguous (VUCA) environment, the rapid digital revolution occurring in our surroundings, and the emergence of the next generation within our organizations. This study presents a framework for successfully incorporating and applying several leadership paradigms in exploratory, reflective, and analytical operations. Effective leadership in the digital era necessitates the use of a variety of leadership styles. Companies must succeed in integrating into the varied and inclusive work environment required by modern society. Achieving the desired results requires not just the abandonment of past methods but also the commitment to applying “next practices”. The current leadership concepts should be in accordance with the prevailing working conditions and beliefs of the current employee and those of future employees. By adopting the viewpoint of the “next up”, existing leadership theories can better accommodate the emotional, historical, and intrinsically imperfect situations that present leadership usually perceives and utilizes to evaluate its activities. The complex structure of this study’s framework enables the use of a single, collaborative, robust leadership model to drive rapid and seamless digital transformation in both enterprises and the contexts that initiate and guide such changes. Furthermore, it enables the exploration of the possible benefits of this approach for both the leaders and team members who struggle with the complexity of these adjustments.